Performance analysis of IEEE 802.22 wireless regional area network in the presence of digital video broadcasting – second generation terrestrial broadcasting services - Popescu, Vlad; Fadda, Mauro; Murroni, Maurizio (Wiley, 2016)
In Cognitive Radio (CR) networks unlicensed secondary users aim at transmitting in licensed bands while preserving primaries from harmful interference. CR communications have been especially studied in the white spaces of TV band (TVWS), defined as the TV free channels left unused in each territorial area by the reallocation of TV services as a direct consequence of the switchover plans. The first full CR standard, the IEEE 802.22 Wireless Regional Area Network (WRAN), has been developed to bring wireless broadband access to remote, rural areas where other wireless networks are not present due to low revenue impact or critical network deployment. IEEE 802.22 WRAN devices are designed to operate in the range of frequencies between 54MHz and 862MHz alongside digital terrestrial television (DTT) operation. In this work we perform a complete analysis to evaluate the performance of IEEE 802.22 WRAN devices coexisting with DVB-T2 adjacent channel transmission in the TV bands in a rural environment. The link budget analysis for IEEE 802.22 WRAN in different coexistence scenarios, such as fixed DTT reception with indoor/outdoor IEEE 802.22 WRAN reception shows that its robustness is comparable to long term evolution (LTE) which represents the state-of-the art of cellular networks in rural scenario